Staff's Activities Web Database System - Fariza Hanim, Rusly (2002)

(untitled)
People are the most valuable asset of any organization. Therefore, the need for executive Human Asset Management is undeniable. One important area that supports successful Human Asset Management is good records management of staff's progress. Thus, there must be an effective way of keeping records of each staff's activities. The boost of Information Technology application provides opportunities for organizations to manipulate the technology in order to improve the effectiveness and efficiency of their operations. One example is the development of computerized record management system using database system, which now has expanded its' capabilities with the introduction of web driven database system. The tremendous growth of this technology offers the ability to transfer large amount of stored and organized data on demand. As a result, powerful and scalable data has been a crucial component of today's web applications. The evolution of this technology has in turn supports the development of new record management software, whether develop internally or through outsourcing. There are numerous methodologies that could be adhered to in system development process. Thus, developers must carefully select the methodology that is suit with own systems needs to be followed. This report will discuss about the development of Staff's Activities Web Database System. It could be seen as an introductory work to a new dimension of record management system, which is based on the web application. This system is develop based on the Database Life Cycle approach. Even though the system is initially designed for the School of Accountancy, UUM, the structure and functions developed are flexible. Thus, this system could be used as a model or reference by other departments or schools in order to develop a similar system in future. Last but not least, some issues and challenges related to the system design and development has also been discovered in this project.